Reversal of ischemia of donor artery myocardium after recanalization of a chronic total occlusion. Issue 4 (3rd July 2013) - Sachdeva, Rajesh; Agrawal, Mayank; Flynn, Shawn E.; Werner, Gerald S.; Uretsky, Barry F.
<x xml:space="preserve">Abstract</x> Background Case reports have shown that an intermediate stenosis in the donor artery collateralizing the myocardium of a chronic total occlusion (CTO) can produce an ischemic fractional flow reserve (FFR) value which may revert to non‐ischemic with CTO revascularization. Methods A consecutive series of patients with severe angina in which a donor artery with intermediate stenosis (30–70%) had FFR measured before and after successful CTO recanalization were studied. Results Fourteen of 50 consecutive CTO patients with successful PCI fulfilled the study criteria. Eight had CTO of the right coronary artery (RCA), three circumflex (LCx), and three RCA and LCx. Left anterior descending artery was the donor artery in 13 and LCx in 1 patient. Of nine donor ischemic FFR patient's pre‐PCI, six reverted to non‐ischemic (FFR pre‐PCI 0.76 ± 0.04 and 0.86 ± 0.03 post‐PCI). Five patients had normal FFR in the donor artery pre‐ and post‐CTO PCI. Conclusions In patients with a CTO and an intermediate donor artery stenosis, the frequency of ischemia in the donor artery territory is relatively high and often normalized by successful CTO recanalization. These data recommend recanalizing the CTO first whenever possible as a preferred therapeutic strategy to avoid the need for PCI to the donor artery or multivessel bypass surgery. © 2013 Wiley Periodicals, Inc.